Redescription of Garra turcica from southern Anatolia (Teleostei: Cyprinidae) - Bayçelebi̇ Esra; Kaya, Cüneyt; Turan, Davut; Ergüden Si̇bel Alagöz; Freyhof, Jörg (Zootaxa, 2018)
Garra turcica, from the rivers Kızıl, Seyhan, Ceyhan and Arsuz, is re-diagnosed and re-described. The species was treated as a synonym of G. rufa but molecular data strongly suggest that G. turcica represent an own species. It is distinguished from G. rufa by being more slender bodied, having a blunt snout and usually a short rostral cap. Based on COI sequence data, G. turcica is closely related to a group of species from the Persian Gulf basin, all having very small distribution areas nested in or adjacent to the range of G. rufa. The closest relatives of G. turcica are G. elegans, G. mondica and G. amirhosseini from which G. turcica differs by having a free posterior edge of the mental disc, the predorsal back covered by scales and the scales on the chest about as large as on the belly as well as by a minimum K2P distance of 2.2% in its COI barcode region.